1997
DOI: 10.1021/jp9631137
|View full text |Cite
|
Sign up to set email alerts
|

Variations and Temperature Dependence of the Excited State Properties of Conformationally and Electronically Perturbed Zinc and Free Base Porphyrins

Abstract: The photophysical properties and their temperature dependence are reported for the sterically encumbered nonplanar zinc and free base 2,3,5,7,8,10,12,13,15,17,18,20-dodecaphenylporphyrins (ZnDPP and H2DPP), and 2,3,7,8,12,13,17,18-octaethyl-5,10,15,20-tetraphenylporphyrins (ZnOETPP and H2OETPP), and the zinc complex of 5,10,15,20-tetra-tert-butylporphyrin (ZnT(t-Bu)P). Compared to planar 5,10,15,20-tetraphenylporphyrins (ZnTPP and H2TPP), the above compounds exhibit reduced lifetimes of the lowest excited sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
151
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(168 citation statements)
references
References 35 publications
16
151
0
Order By: Relevance
“…The reduced porphyrin macrocycle occurs in the pheophytins and, further complexed with magnesium, in the chlorophylls both of which are involved in light harvesting and the transformation of trapped sun light into stored chemical energy in the course of photosynthesis [74]. Because of this significance as biological reaction centers, but also because of their function as photosensitizers in photodynamic therapy and as catalysts in precision macromolecular synthesis [75,76], porphyrins have been the focus of a series of time-resolved spectroscopic investigations over the past years in order to gain a better insight into the internal excited-state dynamics [77][78][79][80][81][82][83][84][85]. For these studies a wide variety of time-resolved techniques has been used including transient absorption, nonlinear absorption, fluorescence and also four-wave-mixing spectroscopy.…”
Section: Protochlorophyllide Amentioning
confidence: 99%
“…The reduced porphyrin macrocycle occurs in the pheophytins and, further complexed with magnesium, in the chlorophylls both of which are involved in light harvesting and the transformation of trapped sun light into stored chemical energy in the course of photosynthesis [74]. Because of this significance as biological reaction centers, but also because of their function as photosensitizers in photodynamic therapy and as catalysts in precision macromolecular synthesis [75,76], porphyrins have been the focus of a series of time-resolved spectroscopic investigations over the past years in order to gain a better insight into the internal excited-state dynamics [77][78][79][80][81][82][83][84][85]. For these studies a wide variety of time-resolved techniques has been used including transient absorption, nonlinear absorption, fluorescence and also four-wave-mixing spectroscopy.…”
Section: Protochlorophyllide Amentioning
confidence: 99%
“…We found earlier [20] that the energy of the charge-transfer (CT) state for OEP-Ph(o-NO 2 ) in toluene exceeds the energy of the locally excited T 1 state by 0.24 eV. Therefore, from energy considerations, the new bands observed cannot be assigned to the T 1 CT absorption transitions. A manifestation of the intrinsic absorption in a system of the states of the ion-radical pair is also unlikely because of a fast transition from the 3 [P + … ] CT state to the lower-lying T 1 state (E CT > E T1 [20]).…”
Section: Induced Absorption Spectramentioning
confidence: 93%
“…Recent spectral, kinetic, and physicochemical studies [1][2][3][4] showed that a number of "hybrid" porphyrins with the steric hindrance (free bases and complexes with metals Ni, Cu, and Fe) have the nonplanar porphyrin macrocycle in the initial S 0 state, which is manifested in a considerable change in the absorption spectrum (strong bathochromic shift and broadening of the bands) and in redox properties compared to planar tetrapyrrole macrocycles. Upon excitation of such molecules, the dynamic conformational mobility of the tetrapyrrole macrocycle in the S 1 state is manifested in strong deformations of the fluorescence spectra (bathochromic shift and broadening of the bands, an increase in the Stokes shift) and in a strong decrease in the quantum yield ϕ F and shortening of the fluorescence lifetime τ S .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations